An RFID localisation system using Dynamic Range Adjustment Localisation. (18th November 2009) - Huang, Chieh-Ling; Chung, Pau-Choo; Tsai, Ming-Hua
This paper presents a position estimation algorithm for moving object based on active RFID. The aim is to achieve enough accuracy of moving object position. In this paper, we propose a Dynamic Range Adjustment Localisation (DRAL) algorithm to locate the moving object associated with the target tag. In DRAL algorithm, reference tags are used as reference basis for dynamically estimating the parameters of each field generator dynamically. Experimental results show that the DRAL algorithm could reduce the impact of the environmental factor on radio frequency signal effectively and have more accurate result.